2010
DOI: 10.4317/medoral.15.e347
|View full text |Cite
|
Sign up to set email alerts
|

Osteolipoma of the buccal mucosa

Abstract: Lipomas are benign mesenchymal neoplasms of soft tissue that can be found in any part of the human body. Conversely, their presence in the oral mucosa is rather uncommon, with approximately 4% of the cases occurring in the oral cavity. In such cases, they are likely to have originated from mature adipose tissue and to be among several described histological variants of lipomas, which are identified according to the predominant type of tissue. There is a rare lipoma, known as an osteolipoma or an ossifying lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 12 publications
3
39
0
1
Order By: Relevance
“…A review of the English literature found that, outside the head and neck area, lipomas with osseous differentiation have been reported in deep locations adjacent to bone tissue in the thigh [10][11][12][13], knee [14,15], sternoclavicular region [16], shoulder [17], wrist [14], hand [18], intraspinal [19] or in superficial subcutaneous tissue [20,21]. More than 60 % of the cases occur in the head and neck region, where they have been described in intraspinal [22], intracranial [23] (suprasellar/hypothalamic and interhemispheric) and extracranial-extraspinal locations [3][4][5][6][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The latter are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English literature found that, outside the head and neck area, lipomas with osseous differentiation have been reported in deep locations adjacent to bone tissue in the thigh [10][11][12][13], knee [14,15], sternoclavicular region [16], shoulder [17], wrist [14], hand [18], intraspinal [19] or in superficial subcutaneous tissue [20,21]. More than 60 % of the cases occur in the head and neck region, where they have been described in intraspinal [22], intracranial [23] (suprasellar/hypothalamic and interhemispheric) and extracranial-extraspinal locations [3][4][5][6][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The latter are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…As for the gender more affected, the majority of studies show no preference 1,2,[11][12][13][14]18 , although there have been reports of localized lipomas in the oral and maxillofacial region 6 in which the male sex is predominant 6,20 but, equally, there have been studies stating a preference for the female sex 3,5,8,10 . 20 , panoramic x-ray of the maxillary region, in the case of intraosseous lipomas 2,11 , magnetic resonance imaging 14,16 and computerized tomography 7 , the latter being cited as the resource of choice for giant facial lipoma.…”
Section: Discussionmentioning
confidence: 99%
“…As for the treatment of lipomas, conservative surgical removal is the method most recommended in cases where they are heavily encapsulated, with minimum possibility of recurrence or risk to adjacent structures 1,9,[12][13][14][15][16][19][20] . When it is not an encapsulated lesion, the risks of recurrence of the lesion are greater due to the difficulty of dissection, which could even affect the facial nerve 18 , which would lead the patient to suffer surgical consequences, compromising function and esthetics of the stomatognathic system 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations